Low phase noise microwave frequency synthesizer for cold atom clock - Mingyuan Yu; Yaning Wang; Jinyin Wan; Xin Wang; Xinchuan Ouyang; Ling Xiao; Tang Li; Huadong Cheng; Liang Liu (AIP Advances, 2019)
We present a low phase noise microwave frequency synthesizer for the integrating sphere cold atom clock. The synthesizer is based on an ultralow-phase-noise oven-controlled crystal oscillator and employs a phase-locking technique. The absolute phase noise performance of the 6834 MHz signal was measured to be −60 and −120 dBc/Hz at offset frequencies of 1 Hz and 10 kHz, respectively. For the new scheme, the direct digital synthesizer is used to tune the clock output. The frequency tuning resolution was improved to 3.4 × 10−15. This scheme for the microwave frequency synthesizer can also be used in other precision measurements.